Produtividade e qualidade fisiológica de sementes de soja em função de estádios de dessecação com PARAQUAT e DIQUAT - Benedet, Daiane Lais (2018)
Desiccation is a strategy for harvest anticipation that may vary depending on which stage of the plant’s development the herbicide is applied. The objective of this work was to evaluate the productivity and the physiological quality of soybean seeds due to desiccation at different physiological stages and herbicides. The study of the culture was conducted in an Eutrophic Red Latosol in the city of Cascavel, PR. The experimental design was randomized blocks, in a 2 × 4 + 1 factorial scheme, two herbicides (paraquat and diquat) applied in four phenological stages, R6, R7.1, R7.2 and R7.3, corresponding to 10, 25, 50, and 75% yellowing of leaves and pods, respectively, with one control (no desiccation) and three replicates. The cultivar NA 5909 RG was used. The weight of one thousand seeds, the productivity and the physiological properties of the seed were evaluated through the tetrazolium test. Chemical desiccation with paraquat resulted in higher grain yield (3,961 kg ha-1) compared to diquat (3,317 kg ha-1), although similar to control (4,221 kg ha-1). Desiccation did not affect the productivity and weight of one thousand soybean seeds. Desiccation with 75% yellowing of leaves and pods (R7.3) showed lower electrical conductivity and higher germination of soybean seeds. Early desiccation with 10 and 25% yellowing of leaves and pods decreases vigor from the tetrazolium test, seed viability and results in moisture damage. It was concluded that early chemical desiccation does not affect the yield of soybeans, however, impairs the physiological quality of the seeds.